Globalizing health benefits for developing countries - Díaz-Bonilla, Eugenio; Babinard, Julie; Pinstrup-Andersen, Per; Thomas, Marcelle (International Food Policy Research Institute, 2002)
For the health community, globalization offers opportunities but also poses important challenges. Dramatic progress has been made in the area of health over the past forty years; however, improvements have been unequally distributed across regions. Developing countries share a disproportionate burden of avoidable mortality and disability, primarily attributable to preventable infectious diseases, malnutrition, and complications of childbirth. Globalization affects global health, which in turn may improve or worsen the health of the poor in developing countries. This paper reviews the different meanings of globalization and indicators for some of its components. Using a simple framework, it examines the channels, which links globalization and health outcomes and identifies among them five main pathways. The first two pathways connect globalization with general outcomes on the economy and the government of developing countries, which affect the global health situation. The last three connect directly globalization with health, through its effect on institutions, nutrition, and the environment. In conclusion, this paper presents some policy and institutional responses that seek to reduce the negative and enhance the positive effects of globalization on health in developing countries